Analysis of specific symptoms of patients after removal of breast cancer with the use of questionnaire QLQ-BR23 - Benirowska, Sylwia (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2018)
Introduction The World Health Organization as the main task, set himself to care about the good quality of life in patients after anti¬cancer treatment. Aim The aim of the study is the analysis of specific symptoms in patients after removal of breast cancer with the use of questionnaire QLQ-BR23. Material and methods The study was conducted among 100 patients. The study uses a questionnaire QLQ-C23. Results The discomfort of the patient concerned to taste the food, feel sick/bad, feels pain in the arm or shoulder, swelling of shoulder or arm, difficulty lifting up the arm, swelling of the affected mammary gland responses remained at the average level. Conclusions These problems clearly decreased in the patients satisfaction from life.